West Nile virus encephalitis in haematological setting: report of two cases and brief review of the literature - Isacco Ferrarini; Antonella Rigo; Alberto Gandini; Fabrizio Vinante (Mediterranean Journal of Hematology and Infectious Diseases)
West Nile virus is a zoonotic agent causing life-threatening encephalitis in a proportion of infected patients. Older age, immunosuppression and mutations in specific host genes (e.g. CCR5 delta-32 mutation) predispose to neuroinvasive infection. We report on two cases of severe West Nile encephalitis in recently-treated, different-aged, chronic lymphocytic leukemia patients. Both patients developed high-grade fever associated with severe neurological impairment. The younger one harboured germ-line CCR5 delta-32 mutation, which might have played a role in the pathogenesis of its neuroinvasive manifestations.